Survival Rate on a 10-Year Follow-Up of Total Wrist Replacement Implants: A 23-Patient Case Series - Honecker, Sophie; Igeta, Yuka; Al Hefzi, Ali; Pizza, Chiara; Facca, Sybille; Liverneaux, Philippe A. (Journal of Wrist Surgery, 2019)
Background According to current literature, the estimated average survival rate for Remotion, the total wrist implants, is above 90% on an 8-year follow-up. We examined our series of Remotion to calculate its survival rate on a 10-year follow-up.Case Description A total of 23 cases of total wrist implants were reviewed. The case series included 22 patients, 18 females and 4 males, of an average age of 55 years. The case series included 19 inflammatory rheumatic diseases, 3 Kienböck disease, and 1 posttraumatic arthrosis.Conclusion The average survival rate of our case series was 95.7% on a 4-year follow-up, 91.3% on a 6-year follow-up, and 69% on a 10-year follow-up. On our review, the QuickDASH score, pain, wrist extension range of motion, and grip strength were improved postoperatively. No difference was shown between preoperative and postoperative values for wrist flexion, pronation, and supination. The case series included a septic case, treated by arthrodesis, and three total wrist implants displacements, two of which were treated by carpal implant, and the remaining one was treated by arthrodesis.Clinical Relevance The survival rate of the total wrist replacement implant Remotion was estimated to be 69%.
Keywords: implant; wrist; rheumatoid arthritis; TWA